Study on patient satisfaction in the government allopathic health facilities of Lucknow district, India - Kumari Ranjeeta; Idris M; Bhushan Vidya; Khanna Anish; Agarwal Monika; Singh S (Wolters Kluwer Medknow Publications, 2009)
Background: The outcome of any disease is influenced by the decisions to seek care, timely arrival at appropriate diagnostic and treatment services and the receipt of adequate care from service providers. Satisfaction in service provision is increasingly being used as a measure of health system performance. Satisfaction manifests itself in the distribution, access and utilization of health services. Objectives: To determine the areas and causes of low satisfaction among the patients and suggest methods for improvement. Materials and Methods: Multistage stratified random sampling was used to select the government allopathic health facilities of Lucknow district and systematic random sampling for the selection of the patients for the interview. Results: The accessibility was difficult in 42% patients and waiting time more than 30 min for 62.5% of those attending the tertiary level health facility. The satisfaction with the duration of the outpatient department (OPD) (64.6%) and the presence of signboards (46.6%) was also found to be low. The overall satisfaction regarding the doctor-patient communication was more than 60% at all the levels of health care facilities but that with the examination and consultation was less than 60% at the primary level as compared to more than 80% elsewhere. The most important motivating factor for the visit to the tertiary (48.2%) and secondary level (71.9%, 67.1%) of health facilities was the faith on doctors or health facility. Conclusions: The level of patient satisfaction is severely deficient in several areas and needs improvement for the achievement of optimal health of the people.